Modification of substrate specificity of l-arginine oxidase for detection of l-citrulline - Kei Yamamoto; Yosuke Masakari; Yasuko Araki; Atsushi Ichiyanagi; Kotaro Ito (AMB Express, 2023)
Abstract Enzymatic detection of citrulline, a potential biomarker for various diseases, is beneficial. However, determining citrulline levels requires expensive instrumental analyses and complicated colorimetric assays. Although l-amino acid oxidase/dehydrogenase is widely used to detect l-amino acids, an l-citrulline-specific oxidase/dehydrogenase has not been reported. Therefore, in this study, we aimed to develop an l-citrulline-specific enzyme by introducing a mutation into l-arginine oxidase (ArgOX) derived from Pseudomonas sp. TPU 7192 to provide a simple enzymatic l-citrulline detection system. The ratio of the oxidase activity against l-arginine to that against l-citrulline (Cit/Arg) was 1.2%, indicating that ArgOX could recognize l-citrulline as a substrate. In the dehydrogenase assay, the specific dehydrogenase activity towards l-arginine was considerably lower than the specific oxidase activity. However, the specific dehydrogenase activity towards l-citrulline was only slightly lower than the oxidase activity, resulting in improved substrate specificity with a Cit/Arg ratio of 49.5%. To enhance the substrate specificity of ArgOX, we performed site-directed mutagenesis using structure-based engineering. The 3D model structure indicated that E486 interacted with the l-arginine side chain. By introducing the E486 mutation, the specific dehydrogenase activity of ArgOX/E486Q for l-citrulline was 3.25 ± 0.50 U/mg, which was 3.8-fold higher than that of ArgOX. The Cit/Arg ratio of ArgOX/E486Q was 150%, which was higher than that of ArgOX. Using ArgOX/E486Q, linear relationships were observed within the range of 10–500 μM l-citrulline, demonstrating its suitability for detecting citrulline in human blood. Consequently, ArgOX/E486Q can be adapted as an enzymatic sensor in the dehydrogenase system. Graphical Abstract